Analisis Perubahan Kebijakan Luar Negeri Iran Menyepakati JCPOA pada Masa Pemerintahan Hassan Rouhani - Abdullah, Abdullah (Jurnal ICMES, 2021)
At the end of 2013, Iran agreed to the P5+1 joint agreement, which became the forerunner of the Joint Comprehensive Plan of Action (JCPOA), signed on July 14, 2015. Iran signed the deal to make the international community recognize its nuclear program and lift sanctions against the country. Previously, from 2003 to 2012, Iran had always refused to negotiate with the West. This phenomenon raises the research question discussed in this article: what causes Iran's policy change regarding its nuclear project. The research was conducted by literature study, utilizing official documents and mass media reports. In this study, the author uses the theory of foreign policymaking as described by Snyder et al. The result obtained is that the changing of Iranian foreign policy was influenced by the internal factors, especially the political and economic dynamics under President Hasan Rouhani. External factors also became the impetus for Iran to change its policies, including the policy changes made by Obama in the second term of his leadership and the endorsement of the deal from the European Union, Russia, and China.